Pengaruh Penerapan E-Filling Dan E-Billing Terhadap Kepatuhan Wajib Pajak (Studi Kasus Di PT. Astra Internatonal Tbk-Tso Auto 2000 Bogor Yasmin) - Pebrianti, Gina; Rumiasih, N.A; Riani, Desmy (Accounting Global Journal, 2022)
This study aims to determine the effect of the implementation of E-Filing and E-Billing on taxpayer compliance in PT. Astra Internasional Tbk-Tso Auto 2000 Bogor Yasmin, This study uses quantitative research methods, using questionnaires and interviews. This study uses primary data where the data is sourced directly from PT. Asta Internasional Tbk-Tso Auto 2000 Bogor Yasmin. The sample in the study used the Convenience Sampling Technique and obtained as many as 50 respondents. The regression analysis model used in this study is multiple linear regression analysis. Where the research results are in the form of exposure rather than statistical results that have been processed using SPSS v Software. 25. Based on the analysis that has been carried out in this study, the results obtained that related to the effect of the application of the E-Filing and E-Billing variables have a positive and significant influence on the Taxpayer Compliance variable.